Modernization and issues of overcoming identiﬁ cation crisis (Journal of Philosophy Culture and Political Science, 2019)
This article considers one of the most topical issues of modern society problem of modernization. Author underlines signiﬁ cance of modernization for development of Independent Republic of Kazakhstan. If to take into account, that material values are higher evaluated than spiritual values in the process of modernization, we must not forget about evolvement of spiritual values of a country. As source for development of spiritual values author offers ideology of idea of nationalism as one of the main factors in development of spiritual side of people.